Experimental study of the albedo of a beam of y rays produced by ultrarelativistic electrons; Soviet Physics Journal; Vol. 34, iss. 6 - Vnukov I. E.; Vorob'ev S. A.; Kalinin B. N.; Lobanov O. Yu.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Stibunov V. N. Victor Nikolaevich; Zabaev V. N. Viktor Nikolaevich (1991, 1991)
Title screen